K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

2 tháng 8 2021

Trả lời:

7, 49y2 - x2 + 6x - 9

= 49y2 - ( x2 - 6x + 9 )

 = ( 7y )2 - ( x - 3 )2

= ( 7y - x + 3 ) ( 7y - x - 3 )

8, sửa đề: 25x2 - 4y2 - 4y - 1

= 25x2 - ( 4y2 + 4y + 1 )

= ( 5x )2 - ( 2y + 1 )

= ( 5x - 2y - 1 ) ( 5x + 2y + 1 )

9, 4x2 - y2 + 8y - 16

= 4x2 - ( y2 - 8y + 16 )

= ( 2x )2 - ( y - 4 )2

= ( 2x - y + 4 ) ( 2x + y - 4 )

2 tháng 8 2021

a, \(49y^2-x^2+6x-9=49y^2-\left(x-3\right)^2=\left(7y-x+3\right)\left(7y+x-3\right)\)

b, đề sai rồi bạn 

c, \(4x^2-y^2+8y-16=4x^2-\left(y-4\right)^2=\left(2x-y+4\right)\left(2x+y-4\right)\)

2 tháng 8 2021

a, \(x^3+3x^2-\left(x+3\right)=0\Leftrightarrow x^2\left(x+3\right)-\left(x+3\right)=0\)

\(\Leftrightarrow\left(x-1\right)\left(x+1\right)\left(x+3\right)=0\Leftrightarrow x=1;x=-1;x=-3\)

b, \(15x-5+6x^2-2x=0\Leftrightarrow5\left(3x-1\right)+2x\left(3x-1\right)=0\)

\(\Leftrightarrow\left(2x+5\right)\left(3x-1\right)=0\Leftrightarrow x=-\frac{5}{2};x=\frac{1}{3}\)

c, \(5x-2-25x^2+10x=0\)

\(\Leftrightarrow\left(5x-2\right)-5x\left(5x-2\right)=0\Leftrightarrow\left(1-5x\right)\left(5x-2\right)=0\Leftrightarrow x=\frac{2}{5};x=\frac{1}{5}\)

= 1/5 nha

3 tháng 8 2021

Trả lời:

\(3x\left(x-7\right)+2x-14=0\)

\(\Leftrightarrow3x\left(x-7\right)+2\left(x-7\right)=0\)

\(\Leftrightarrow\left(x-7\right)\left(3x+2\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x-7=0\\3x+2=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=7\\x=-\frac{2}{3}\end{cases}}}\)

Vậy x = 7; x = - 2/3 là nghiệm của pt.

2 tháng 8 2021

sửa đề :

 \(3x\left(x-7\right)+2x-14=0\Leftrightarrow3x\left(x-7\right)+2\left(x-7\right)=0\)

\(\Leftrightarrow\left(3x+2\right)\left(x-7\right)=0\Leftrightarrow x=-\frac{2}{3};x=7\)

2 tháng 8 2021

\(x^2y+y^2x+x^2z+z^2x+y^2z+z^2y+2xyz\)..

\(=\left(x^2y+z^2y+2xyz\right)+\left(y^2x+y^2z\right)+\left(z^2x+x^2z\right)\).

\(=y\left(x+z\right)^2+y^2\left(x+z\right)+xz\left(x+z\right)\)

\(=\left(xy+yz\right)\left(x+z\right)+\left(x+z\right)\left(y^2+xz\right)\).

\(=\left(x+z\right)\left(xy+yz+y^2+xz\right)\).

\(=\left(x+z\right)\left[x\left(y+z\right)+y\left(y+z\right)\right]\).

\(=\left(x+z\right)\left(x+y\right)\left(y+z\right)\).

2 tháng 8 2021

fdkrycyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyydr 

DD
2 tháng 8 2021

\(\left(a+b+c\right)^2+a^2+b^2+c^2\)

\(=a^2+b^2+c^2+2ab+2bc+2ca+a^2+b^2+c^2\)

\(=a^2+2ab+b^2+b^2+2bc+c^2+c^2+2ca+a^2\)

\(=\left(a+b\right)^2+\left(b+c\right)^2+\left(c+a\right)^2\)

2 tháng 8 2021

x=67e